1974
DOI: 10.1002/mrc.1270060907
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐13 NMR spectra of retinal1 and its related compounds

Abstract: Abstract-Carbon-13 NMR spectra of all-trans retinal, and vitamin A, were measured by the pulse Fourier transform method in CCI,. All peaks in these spectra were assigned from considerations of chemical shifts, half proton-decoupled spectra, spin-lattice relaxation times and induced chemical shift by the addition of shift reagent. The carbon-13 NMR spectrum was also measured for all-trans retinal, which had been exposed to the sunlight for three hours, and the induced isomer was proposed to be 1 1-s-cis retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several reports have dealt with 13C n. m. r. spectroscopy of retinals (53,54,158,159). Systems studied include all-trans-retinal (606) (53,54,158,159), 9-cis-retinal (607) (53,54), ll-cis-retinal (608) (53, 54) and 13-cis-retinal (609) (53,54).…”
Section: Carotenoids and Related Terpenoidsmentioning
confidence: 99%
“…Several reports have dealt with 13C n. m. r. spectroscopy of retinals (53,54,158,159). Systems studied include all-trans-retinal (606) (53,54,158,159), 9-cis-retinal (607) (53,54), ll-cis-retinal (608) (53, 54) and 13-cis-retinal (609) (53,54).…”
Section: Carotenoids and Related Terpenoidsmentioning
confidence: 99%
“…Previous experimental work on the most appropriate model of the chromophore of rhodopsin, i.e., a protonated 11cis Schiff base, has been limited (Erickson & Blatz, 1968; Johnston & Zand, 1973; Poincelot et al, 1970;Alchalel et al, 1975;Menger & Kliger, 1976;Mathies et al, 1977). Other model systems have included retinal isomers (Patel, 1969;Becker et al, 1974; Inoue et al, 1974), various all-trans (Blatz et al, 1972;Rosenfeld et al, 1974;Schaffer et al, 1974), 9-cis, 11-cis, and 13-cis (Schaffer et al, 1974;Rosenfeld et al, 1974) Schiff bases of retinal, and protonated all-trans (Waddell et al, 1973; Fisher & Weiss, 1974; Adams et al, 1974;Blatz et al, 1972; Mathies & Stryer, 1976;Tokito et al, 1975), 9-cis, and 13-cis (Adams et al, 1970) Schiff bases of retinal. We report here the preparation and a and 13C NMR study of N-( \ 1-cA-retinylidene)propylimine (NRPI,1 ***arbitrarily shown in the 12s-cis conformation) and its trifluoroacetate and chloride salts (NRPI-HC1, II, shown in the 12-s-trans conformation).…”
mentioning
confidence: 99%